Knowledge, attitudes and practices of primary care professionals about the food guide for children up to 2 years old: a cross-sectional study, Botucatu, Sao Paulo, 2023 - Amaral, Vivian Lovison do [UNESP]; Spadotto, Giovana Canela [UNESP]; Gomes, Caroline de Barros [UNESP] (Ministerio Da Saude, 2024)
Objective: To investigate the knowledge, attitudes, and practices of primary health care professionals regarding breastfeeding and complementary feeding, according to the recommendations of the dietary guide for Brazilian children under 2 years of age. Methods: This is a descriptive study carried out from October to December 2023, using a self-administered online questionnaire aimed at physicians, nurses, and community health agents working in primary health care in Botucatu, Sao Paulo. A descriptive analysis and association between professional categories and their knowledge, attitudes, and practices regarding the content of the guide were performed using Pearson's chi-square test. Results: A total of 74 professionals participated, including 37 community health agents, 19 nurses, and 18 physicians. Half of the professionals had low knowledge about the content of the guide, answering less than half of the questions correctly, with special emphasis on those related to complementary feeding, in which 57 professionals answered less than half of them correctly. Physicians and nurses were the professionals who believed they were more qualified to pass on information related to the content of the guide, when compared to community health agents (p-value <0.001). Regarding practices, 18 professionals claimed to sometimes provide guidance on breastfeeding, 24 claimed to never assess breastfeeding during consultations and home visits, and 22 of them provide guidance on the introduction of complementary feeding. Conclusion: The knowledge of physicians, nurses, and community health agents was deficient in relation to the content of the guide. Attitudes and practices regarding such content were also compromised.
Keywords: Breastfeeding; Infant Nutrition; Food Guides; Primary Health Care; Cross-Sectional Studies